CASE STUDY OF PLAY THERAPY USING HAND PUPPETS TO IMPROVE LANGUAGE SKILLS IN CHILDREN - Firmansyah, Andan; Sukaesih, Iis (Bina Generasi : Jurnal Kesehatan, 2024)
Objective: The purpose of this case study is to carry out nursing care for children and to see the effectiveness of the play therapy approach that uses hand puppets for language skills problems. Method: The method used is descriptive qualitative with a case study approach. as well as pre-test intervention and post-test intervention. This nursing care was carried out for three days using terami intervention playing with hand puppets. The subject of this case study is a child who has a speech delay. With data collection techniques including interviews, observation, physical examination and documentation. Result: The results of the case study at the review stage found that An.R language skills were just beginning to develop with a diagnosis of verbal communication disorder related to environmental barriers characterized by not wanting to socialize and communicate with people, showing inappropriate responses. Interventions and implementations used to improve language skills and verbal communication disorders are Play Therapy Using Hand Puppets to Improve Language Skills in Children. Conclusion: During the intervention at four meetings, there was a slight increase in the client's language skills from starting to develop to developing as expected with a value of filling out the questionnaire on the first day of 47.5 and on the fourth day filling out the questionnaire again with a value of 53.5. As well as this case study has reached the target achievements planned by the researchers, namely increased language skills, increased speaking ability and increased suitability of facial/body expressions.